Predicting the Use of Public Transportation: A Case Study from Putrajaya, Malaysia - Muhamad Nazri Borhan; Deprizon Syamsunur; Norliza Mohd Akhir; Muhamad Razuhanafi Mat Yazid; Amiruddin Ismail; Riza Atiq Rahmat (The Scientific World Journal)
Putrajaya is a new federal administrative capital of Malaysia which has been set to achieve a 70% share of all travels by public transport in the city area. However, the current modal split between the public transport and private transport is 15 : 85. In order to understand travelers’ willingness to use the public transport, a conceptual model has been developed to determine the factors that affect them to use the public transport instead of travelling in their own cars. Various variables such as service quality, environmental impact, attitude, and behavior intention were analyzed and tested using structural equation model (SEM). Results indicate that the service quality and attitude are found to have positive effects on the behavioral intention of taking the public transport. Other than this, this study also shows that the service quality and environmental impact have some positive influences on the attitude to using the public transport. However, environmental impact has no significant, positive, and direct effect on behavioral intention. The results of this study demonstrate that the model that was developed is useful in predicting the public transport and it could provide a more complete understanding of behavioral intention towards public transport use.